Особливості вивчення риторики як дисципліни вільного вибору студента - Куньч, Зоряна; Руденко, Стефанія (Видавництво Львівської політехніки, 2018)
The article deals with the current problem of the specificity of students' free choice study. Rhetoric as a science and art of effective and expedient communication is often chosen by students of different specialties, so there are certain features of the teacher's work in the "team" student groups. The problem points of this work are analyzed and their ways of overcoming are outlined.
Keywords: риторика; дисципліна вільного вибору студента; комунікативна компетентність; навички комунікації; інтерактивні методи навчання